Constructing a Test for the Concept of Sustainable Development of Kindergarten Children (Journal Of Educational and Psychological Researches, 2024)
In order to detect the level of sustainable development among kindergarten children, the two researchers developed a test consisting of 18 items that are characterized by validity and reliability. The study sample consisted of 80 male and female children. After applying the research tool to the sample, the results revealed a weakness in the concept of sustainable development among kindergarten children. The researcher presented a set of recommendations and suggestions